BEBERAPA METODE ITERASI DENGAN TURUNAN KETIGA UNTUK MENYELESAIKAN PERSAMAAN NONLINEAR BESERTA DINAMIKNYA - -, Zulkarnain; Imran, M. (Universitas Pasir Pengaraian, 2014)
Some iterative methods having third-order derivative for solving nonlinearequations are discussed. We compare every iterative method by looking at thebasin of attraction for each method.